Censo de minifuncio en Colombia. - Machado Cartagena, A.; Rodríguez R, M.; Briceño M, H.; Martínez A, G.; Toro N, A. (MINAGRICULTURA-IICA, 2019)
Instituto Interamericano de Cooperación para la Agricultura - IICA